Computer-assisted modeling of Quorum sensing in bacterial population exposed to antibiotics - Kuttler, Christina; Maslovskaya, Anna (Frontiers in Applied Mathematics and Statistics, 2022)
A mathematical model for bacterial growth and control by antibiotics treatment, including Quorum sensing as a special kind of communication, is introduced. We aim in setting up a flexible model structure allowing for fast simulations and overview about the general behaviour. The deterministic approach can be used for in silico studies of bacterial cooperative behavior in the special case of Quorum sensing. Since antibiotic treatment is the basic and vital way to fight pathogenic bacteria, in the present study, we propose a modification of a reaction-diffusion model of communication processes in a bacterial population exposed to antibiotics. The dynamical biological system is formalized by a system of semilinear parabolic PDEs. The numerical solution of the 2D problem is based on a hybrid computing procedure, which includes a finite difference method combined with a Monte-Carlo simulation of population dynamics. Computational experiments are performed to describe space-time distributions of key chemical compounds characterizing Quorum sensing during the growth of a bacterial population and its decrease resulting from the predetermined strategy of antibiotic treatment.